Research on Improvement of Spectrum Efficiency of Spread Spectrum OFDM Communication Scheme for Cruising Sensor Network - Yuan Wang; Zhoumo Zeng; Yibo Li; Wen Zhang; Hao Feng; Shijiu Jin (International Journal of Distributed Sensor Networks)
Cruising sensor nodes have an attractive application in monitoring liquid-based industrial environments. A cruising sensor node, equipped with various sensors, is self-propelled so that they can “cruise” to specified area to gather scientific data. The cruising sensor network consists of an array of such cruising nodes to perform collaborative monitoring task over a given area. A reliable and high-speed underwater acoustic (UWA) communication scheme is necessary for node-to-node communication. Most of the industrial liquid reservoirs are confined spaces, including large oil tanks and nuclear storage ponds. The communication in confined underwater space will suffer more severe multipath interference caused by numerous reflections from boundaries. Conventional orthogonal frequency-division multiplexing (OFDM) technique has poor performance in this channel. Instead, spread spectrum orthogonal frequency-division multiplexing (SS-OFDM), which applies spread spectrum technique into OFDM, has better performance in such severely multipath fading underwater channels. However, the spread spectrum process causes a huge waste in the spectrum efficiency. In order to enhance the transmission efficiency, a mapping sequence spread spectrum OFDM (MSSS-OFDM) method is proposed in this paper. The simulation and experimental results show that our scheme is a robust and spectrum efficient communication method for confined underwater space.